Description of Hardiness in Sales Promotion Girl in Surabaya: Gambaran Hardiness Pada Sales Promotion Girl di Surabaya - Arsa, Sondang Beto Karaeng; Widyastuti, Widyastuti (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the level of hardiness in sales promotion girl. hardiness is a psychological resilience and strategy to deal with stress which can be seen from three aspects, namely, commitment, control and challenge. this research uses descriptive quantitative method. with a population of 50 spg, the sample used is 50 sales promotion girls. the sampling method used in this research is saturated sampling. the data collection method uses a likert scale, namely the hardiness scale. hardiness scale based on kobasa's (1982) theory. the results of data analysis from this study hardiness is in the medium category. the result of further research is the percentage of hardiness aspect that is high is control.